Improvement of transmission efficiency using shielded-loop antenna for wireless power transfer - Kajiura, Naoya; Hirayama, Hiroshi (2016 International Symposium on Antennas and Propagation (ISAP), 2016)
Coupled-resonant wireless power transfer (WPT) using shielded loop antenna for high-efficiency transmission is proposed. Transmission efficiency is determined by the coupling coefficient k and the Q factor. Coupling coefficient k is determined by the difference between the magnetic- and the electric-field coupling coefficient. By using the shielded-loop structure, electric field coupling is suppressed to improve transmission efficiency. Numerical simulation verified that transmission distance over 80% efficiency is extend 2.8 times by using the shielded-loop antenna.